Degradation of AMPK‐α1 sensitizes BRAF inhibitor‐resistant melanoma cells to arginine deprivation. Issue 12 (16th November 2017) - Li, Ying‐Ying; Wu, Chunjing; Shah, Sumedh S.; Chen, Shu‐Mei; Wangpaichitr, Medhi; Kuo, Macus T.; Feun, Lynn G.; Han, Xiaoqing; Suarez, Miguel; Prince, Jeffrey; Savaraj, Niramol
Abstract : Melanomas harboring BRAF mutation (V600E) are known to recur frequently following treatment with BRAF inhibitors (BRAFi) despite a high initial response rate. Our previous study has uncovered that BRAFi‐resistant melanoma (BR) cells are vulnerable to arginine deprivation. It has been reported that naïve melanoma cells undergo autophagy and re‐express argininosuccinate synthetase 1 (ASS1) to enable them to synthesize arginine for survival when encountering arginine deprivation. Abolishing these two factors in BR cells confers sensitivity to arginine deprivation. In this report, we further demonstrated that downregulation of AMPK‐α1 in BR cells is a major factor contributing to impairment of autophagy as evidenced by decreased autophagosome formation. These BR cells also showed a metabolic shift from glucose to arginine dependence, which was supported by decreased expressions of GLUT1 (glucose transporter) and hexokinase II (HKII) coupled with less glucose uptake but high levels of arginine transporter CAT‐2 expression. Furthermore, silencing CAT‐2 expression also distinctly attenuated BR cell proliferation. Notably, when naïve melanoma cells became BR cells by long‐term exposure to BRAFi, a stepwise degradation of AMPK‐α1 was initiated via ubiquitin‐proteasome system (UPS). We discovered that a novel E3 ligase, RING finger 44 (RNF44), is responsible for promoting AMPK‐α1 degradation in BR cells. RNF44 expression in BR cells was upregulated by transcription factor CREB triggered by hyperactivation of ERK/AKT. High levels of RNF44 corresponding to low levels of AMPK‐α1 appeared in BR xenografts and melanoma tumor samples from BR and BRAFi/MEK inhibitor (MEKi)‐resistant (BMR) melanoma patients. Similar to BR cells, BMR cells were also sensitive to arginine deprivation. Our study provides a novel insight into the mechanism whereby BRAFi or BRAFi/MEKi resistance drives proteasomal degradation of AMPK‐α1 and consequently regulates autophagy and metabolic reprogramming in melanoma cells. Abstract : Resistance to BRAF inhibitor attenuates ASS1 expression and enhances RNF44‐mediated AMPK‐α1 degradation. These pathways abrogate autophagy and reprogram metabolism toward exogenous arginine acquisition. Hence, arginine deprivation is very effective to treat BRAF inhibitor‐resistant melanoma cells through the induction of apoptosis.